2021
DOI: 10.1021/acs.jpcc.0c09973
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Formation of Luminescent Centers in Light-Up Ag Cluster-Based DNA Probes

Abstract: Fluorescent beacons based on silver (Ag) clusters for DNA/RNA detection represent a new type of turn-on probe that fluoresces upon hybridization to target nucleobase sequences. Physical–chemical mechanisms of their fluorescence activation still remain poorly understood. We studied in detail the fluorescence activation of dark Ag clusters induced by interactions of Ag–DNA complexes with different DNA sequences. In all cases, the final result depends neither on the location of the precursors (dark clusters) nor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
(99 reference statements)
0
11
0
Order By: Relevance
“…A limited number of studies have shown resolved structures of AgNCs including X-ray crystallography 8,9 and computational reports. 34 Further studies are expected to uncover more details of structural control and reproducibility, making it possible to regulate properties of the nanoclusters both wanted (fluorescence wavelength and intensity) and unwanted (stability).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A limited number of studies have shown resolved structures of AgNCs including X-ray crystallography 8,9 and computational reports. 34 Further studies are expected to uncover more details of structural control and reproducibility, making it possible to regulate properties of the nanoclusters both wanted (fluorescence wavelength and intensity) and unwanted (stability).…”
Section: Resultsmentioning
confidence: 99%
“…It has been recently suggested that the core of the "luminescent" cluster may be different from the size of the full AgNC. 34 Further visualization of molecular orbitals involved in the visible transitions conrmed the highly delocalized properties of the AgNC@hpC 12 . Fig.…”
Section: Optical Transitions Of the Ag 10 Nc@hpc 12mentioning
confidence: 99%
See 1 more Smart Citation
“…Using the software package, you can determine the important characteristics of the electronic states of polyatomic molecules: the energies and nature of molecular orbitals, the energies and wave functions of singlet and triplet electronically excited states, the oscillator strength and polarization of electronic transitions, the distribution of the electron density on the atoms and bonds of the molecule, the dipole moments in ground and excited states, rate constants of radiative and nonradiative processes involving electronically excited states of molecules, as well as absorption spectra from excited singlet and triplet states ( Artyukhov et al, 2008 ; Alfimov et al, 2014 ; Artyukhov et al, 1997 ; Plotnikov, 1979 ; Pomogaev and Artyukhov, 2001 ). Moreover, this software set has achieved success in solving the problems of large molecules photonics ( Plotnikov, 1979 ; Artyukhov and Pomogaev, 2000 ; Bocharnikova et al, 2019 ; Liano et al, 2003 ; Reveguk et al, 2020 ; Tchaikovskaya et al, 2020 ). The methodology for studying the spectral-luminescent properties of complex molecules was described in ( Alfimov and Plotnikov, 2014 ; Bocharnikova et al, 2020 ).…”
Section: Objects and Methods Of Researchmentioning
confidence: 99%
“…Nucleobases preferentially coordinate silvers but with different affinities, so a particular pattern of nucleobase ligands encodes the cluster spectra. ,,, Second, DNA structure shapes binding sites. A single-stranded oligonucleotide can both encapsulate a cluster and hybridize with a complement. , Complementary base pairs block cluster binding sites on nucleobases and force a DNA-bound cluster to reorganize, which can enhance emission by ≲10 3 fold. Third, a flexible DNA wraps around a cluster to give compact and emissive conjugates because hinge sites allow the oligonucleotide to fold. Fourth, DNA strands assemble around a shared cluster.…”
Section: Introductionmentioning
confidence: 99%